THE INFLUENCE OF SELF-EFFICACY AND CREATIVITY TOWARDS ENTREPRENEURIAL INTENTION OF PSYCHOLOGY STUDENTS IN UNIVERSITY OF NORTH SUMATERA - Nasution, Rizky Syahfitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Entrepreneurial intention is one of the elements that can affect growth in entrepreneurship. Entrepreneurial intentions are usually influenced by self-efficacy and creativity. The purpose of this research is to determine the influence of self-efficacy and creativity on entrepreneurial intent. This research involved 123 psychology students from the University of North Sumatra. The data collection methods used are 3 measuring tools named, self-efficacy, creativity, and Torrance Test Of Creative Thinking (TTOCT). The data was analyzed with multiple linear regression. The results of regression analysis show that self-efficacy and creativity affect the improvement of entrepreneurial intent towards students. The results of the implementation of this research are expected to provide an understanding of how self-efficacy and creativity affect students' entrepreneurial intentions and also add insight into the psychology faculty about entrepreneurship, self-efficacy, and creativity descriptions in students.